Herpes simplex encephalitis: involvement of apolipoprotein E genotype. - Lin, W; Wozniak, M; Esiri, M; Klenerman, P; Itzhaki, R (2001)
It was previously found that herpes simplex type 1 virus (HSV1) when present in the brain, is a risk factor for Alzheimer's disease in carriers of the type 4 allele of the gene for apolipoprotein E (apoE epsilon4), and apoE epsilon4 is a risk factor for herpes labialis. Whether a specific allele of the gene is involved in susceptibility to another disorder caused by HSV1-herpes simplex encephalitis (HSE)-has now been investigated. DNA was prepared from formalin-fixed, paraffin-embedded blocks of specimens from the brain or spleen of 14 United Kingdom patients with HSE, confirmed by necropsy, and from the CSF of seven United Kingdom clinical patients with HSV1 in their CSF detected by polymerase chain reaction (PCR). ApoE genotype of the DNA from blocks was determined by seminested PCR, and of the DNA from CSF by one step PCR, followed by restriction endonuclease digestion. The apoE allele frequencies were compared with values previously obtained for 238 normal people from the United Kingdom. The apoE epsilon2 allele frequency of the patients with HSE was 26%, significantly higher than the value of 7% for the normal subjects (OR=4.6, 95% confidence interval (95% CI) 2. 0-10.8). The apoE epsilon3 and epsilon4 allele frequencies did not differ significantly between the two groups. Thus, it seems that apoE epsilon2 is a risk factor for HSE.